Analysis of The Impact of The Tiktok Trend on The Behavior of Female Santri: (Case Study of Students of The Mambaul Ma’arif Islamic Boarding School In Jombang) - Pratama, Dini; Fauzi, Agus Machfud (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
This study aims to analyze the impact of TikTok trends on the behavior of female students (santriwati) at Pondok Pesantren Mamba’ul Ma’arif Denanyar Jombang. As a social media platform for entertainment and creative expression, TikTok has a dual effect: it can positively enhance emotional well-being but also cause dependency that disrupts learning and religious practices. This research employs a qualitative descriptive approach, utilizing interviews and observations to gain an accurate understanding of changes in the santriwati’s behavior. The results indicate that exposure to TikTok content inconsistent with Islamic values encourages the adoption of lifestyles and norms that contradict pesantren teachings, hinders the development of religious knowledge, and weakens religious norms and values. The study applies consumer culture theory to explain the identity formation process influenced by symbolic consumption from social media content. Therefore, it is crucial for pesantren institutions and families to strengthen digital literacy, supervision, and comprehensive religious education, enabling santriwati to use TikTok wisely without compromising Islamic values. These findings are expected to serve as a reference for managing social media use within pesantren environments.